An Analysis and Design of Production System of Bio-plastics from Jackfruit Seeds Starch - Rafika Ratik Srimurni; Wilda Harlia Devita; Rahmi Rismayan Deri (Universitas Darussalam Gontor, 2021)
Bioplastic is an alternative packaging material developed from natural and environmentally friendly ingredients such as protein, polysaccharides, and fat. The high carbohydrate content in jackfruit seeds is possible to applying in produceplastics easily degraded. The composition of the plasticsmaterial from a mixture of jackfruit seeds and plasticizers such as glycerol is still not known the exact formula to obtain optimal physical properties and mechanical strength (tensile strength and elongation at break) from bio-plastics. This research aims to design the production system and determines the composition of bio-plastic materialsto optimize thetensile strength and elongation atbreak bio-plastic from jackfruit seed starch and glycerol. To design the system, BPMN 2.0, Response Surface Methodology (RSM), as well as verification and validationwere applied. The complexity in the bio-plastic production system from jackfruit seed starch to maximize the quality of the bio-plastics has a relationship between one another which is needed in system analysis and design. The verification results show zero error and zero warning at each modeling step. The best formulation of bio-plastics is the composition of starch content to water 6.08% and glycerol content to 30% with a tensile strength value of 0.76 MPa and elongation at break of 6.12%